Cellulose derivatives as effective recrystallization inhibitor for ternary ritonavir solid dispersions: In vitro-in vivo evaluation. (1st December 2021) - Guan, Qingran; Ma, Qisan; Zhao, Yanna; Jiang, Xinxin; Zhang, Huaizhen; Liu, Min; Wang, Zhengping; Han, Jun
Abstract: Amorphous solid dispersions (ASDs) are regarded as one of the most promising techniques for poorly-soluble active pharmaceutical ingredients (API). However, the thermodynamic instability of ASDs at supersaturated state makes them easy to recrystallize in aqueous media. In this study, ritonavir (RTV) was selected as a model drug for evaluating the solubility enhancement and recrystallization inhibition effect of various cellulose derivatives and the combinations of them with typical surfactants. Combination of HPMCAS-HF/SLS was filtrated for preparing ternary RTV solid dispersions (RTV SD) via solvent evaporation method. RTV SD exhibited enhanced dissolution manner, while the oral bioavailability of RTV SD was equivalent with the Reference Standard Norvir® but increased significantly compared to the ternary physical mixture. Thus, the ternary SD system might be promisingly employed as efficient drug delivery system for RTV, while the HPMCAS-HF/SLS combination could be recommended as effective excipient for fabricating steady solid dispersions loading poorly soluble API.